Methods Used for Enhancing the Bioavailability of Oral Curcumin in Randomized Controlled Trials: A Meta-Research Study - Bruna Mimica; Viljemka Bučević Popović; Ines Banjari; Antonia Jeličić Kadić; Livia Puljak (MDPI AG, 2022)
It is unknown how randomized controlled trials (RCTs) approach the problem related to curcumin bioavailability. We analyzed methods and reporting regarding the bioavailability of systemic oral curcumin used in RCTs. We searched PubMed on 12 September 2020, to find articles reporting RCTs that used curcumin as an intervention. We extracted data about trial characteristics, curcumin products used, methods for improving curcumin bioavailability, and mentions of curcumin bioavailability. We included 165 RCTs. The most common category of intervention was simply described as "curcumin" or "curcuminoids" without a commercial name. There were 107 (64%) manuscripts that reported that they used methods to enhance the oral bioavailability of curcuminoids used in their intervention; 25 different methods were reported. The most common method was the addition of piperine (23%). Phospholipidated curcumin, a combination of curcumin and turmeric oils, nanomicellar curcumin, and colloidal dispersion of curcumin were the next most common methods. Fourteen trials (8.4%) compared more than one different curcumin product; nine (7.9%) trials compared the bioavailability/pharmacokinetics of curcumin products. In conclusion, a high number of diverse methods were used, and very few trials compared different curcumin products. More studies are needed to explore the comparative bioavailability and efficacy of different curcumin products.